Deglacial bottom water warming intensified Arctic methane seepage in the NW Barents Sea - El Bani Altuna, Naima; Rasmussen, Tine Lander; Ezat, Mohamed; Vadakkepuliyambatta, Sunil; Groeneveld, Jeroen; Greaves, Mervyn (Communications Earth & Environment, 2021)
Changes in the Arctic climate-ocean system can rapidly impact carbon cycling and cryosphere. Methane release from the seafloor has been widespread in the Barents Sea since the last deglaciation, being closely linked to changes in pressure and bottom water temperature. Here, we present a post-glacial bottom water temperature record (18,000–0 years before present) based on Mg/Ca in benthic foraminifera from an area where methane seepage occurs and proximal to a former Arctic ice-sheet grounding zone. Coupled ice sheet-hydrate stability modeling shows that phases of extreme bottom water temperature up to 6 °C and associated with inflow of Atlantic Water repeatedly destabilized subsurface hydrates facilitating the release of greenhouse gasses from the seabed. Furthermore, these warming events played an important role in triggering multiple collapses of the marine-based Svalbard Barents Sea Ice Sheet. Future warming of the Atlantic Water could lead to widespread disappearance of gas hydrates and melting of the remaining marine-terminating glaciers.